PENGARUH INFLASI, EKSPOR, DAN PEMBAYARAN CICILAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA INDONESIA TAHUN 2004-2019 - Kholifah Fitri; Mayes Anthony; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to know how the influence of inflation, exports, and payments of foreign debt installments on foreign exchange reserves in Indonesian in 2004-2019. This research uses independent variables of Inflation, Exports, and Payments of Foreign Debt Installments and dependent variable is Foreign Exchange Reserves in Indonesian. The data used in this research is annual data from 2004-2019. The analytical method used is descriptive quantitative and analyzed partially or simultaneously with multiple linear regression OLS (Ordinary Least Square) processed by using E-Views 10. The results show that, inflation, exports, and payments of foreign debt installments has a significant effect on foreign exchange reserves in Indonesian in 2004-2019. Meanwhile, inflation has a significant negative effect on foreign exchange reserves in Indonesian, exports has significant positive effect on foreign exchange reserves in Indonesian, and payments of foreign debt installments has no signifikan positive effect on foreign exchange reserves in Indonesian. In addition, it was found that the value of adjusted R2 is 84,37%%.Keywords: Foreign Exchange Reserves, Inflation, Exports, Payments of Foreign Debt Installments